Sacrifice subi ou sauvetage organisé. Le sort des archives en France durant la Grande Guerre, d’après le fonds de la direction ministérielle des Archives - Isabelle Chave (In Situ)
The First World War had a considerable impact on French archive services, as it did on other cultural institutions. Looking at the papers held today by the ministerial archival directorate (direction ministérielle des Archives) and at some local studies concentrating on the departments situated in the North-East of France, it is possible today to have a better understanding of what became of this paper heritage during the war years. As is to be seen in examples of major and selective programs of destruction, in the choice of which holdings were to be protected and evacuated to safety far from the front line, and in territorial tours of inspection and documentation, French archivists were directly implicated in establishing contingency procedures and appropriate responses to the situation of exceptional crisis, often inspired by memories of archives lost during the Franco-Prussian of 1870. This on-going memory of successive conflicts is particularly to be noted in the negotiations of the immediate post-war years: by means of war reparations or by the reconstitution of documentary collections, what was at stake was the recognition of the importance of the damage suffered by heritage.